P-069 Rates, Trends and Predictors of 30-Day Readmission of Crohn's Disease: A National Perspective. (February 2017) - Pathak, Ambarish; Savani, Chirag; Devani, Kalpit; Shah, Harshil; Patel, Rajve; Hazra, Arpita; Narwal, Kriti; Thakore, Kosha; Amin, Aditi; Choudhary, Anita; Mishra, Tushar; Dalapathi, Vijay
Abstract : Background: There is sparse data on real time rates, trends and predictors of readmission rates of Crohn's disease. we aim to find national real time rates, trends and predictors of readmission. Methods: We utilized National Readmission Data (NRD) 2013, a subset of the Healthcare Cost and Utilization Project (HCUP) sponsored by the Agency for Healthcare Research and Quality (AHRQ). Crohn's Disease was identified using ICD 9 code (555.xx) as primary diagnosis. Patients with missing information on age, gender and mortality were removed. Patients with age <18 were removed as well. Patients were followed over next 30 days with help of "NRD_VisitLink" and "NRD_DaysToEvent" variables. Co-morbidities were identified by "cm_" variables in HCUP database. Comorbid conditions were defined by Charlson's Comorbidity Index (CCI). Primary outcome of study was 30-days readmission. We ran 2 level hierarchical logistic model to find out predictors of outcomes. Readmission etiologies were identified with ICD 9 diagnosis codes in primary diagnosis field. Results: Seventeen thousand five hundred ninety-three patients were identified with Crohn's disease, which were national representative of 41, 940. Mean age of patients was 43.8 ± 0.1 and 55.86% of patients were female. 2539/17, 593 (14.43%) patients were readmitted with total of 3001 readmissions over 30 days post discharge. 2149/2539(84.64%), 332/2539(13.08%) and 58/2539 (2.29%) patients were readmitted one, 2 and more than or equal to 3 times respectively. Twenty-five percent, 50% and 75% of readmissions took place in 7, 14 and 23 days respectively. 1232/3001 (41.06%) readmissions were due to Crohn's disease. On multivariate analysis, patients with older age (OR: 95% Confidence Interval [CI], P value) (0.99, 0.98–0.99, P = 0.04), female (0.86, 0.82–0.92, P < 0.001) compared to male, weekend admission (0.91, 0.84–0.98, P = 0.009) compare to weekday, elective admission (0.88, 0.80–0.96, P = 0.003) compared to non-elective, private insurance (0.58, 0.55–0.62, P < 0.001) compare to medicare/medicaid were associated with decreased in readmission. While, higher charlson score (CCI-1:1.27, 1.14–1.43, P < 0.001), (CCI ≥ 2: 1.47, 1.24–1.73, P < 0.001) compared to CCI-0 and comorbidities such as anemia (1.24, 1.17–1.33, P < 0.001) and peripheral vascular disease (1.34, 1.11–1.62, P = 0.002) were associated with increase in readmission. Non influential co morbidities were obesity, liver disease, diabetes, hypertension, renal failure, heart failure, chronic lung disease, arthritis. 40/17, 593 (0.23%) patients died during index admission and 21/3001 (0.7%) patients died during readmission. Conclusions: Patient's with crohn's disease has striking 14% readmission rate regardless of the age. Sicker patient population and population with comorbidities has higher readmission rate. National average of readmission will help institutes to set the bar for their own community and predictors of readmission will help to identify high risk patient population and to do additional intervention to prevent readmissions.